Integration Of Pancasila Values In Ppkn Learning In Primary School Through Football Games - Adi Winata, I Made Oka; Lasmawan, I Wayan; Suastika, Nengah; Bagus Sanjaya, Dewa (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
The cultivation of Pancasila values from a young age is a very important basis for building the character of Indonesia's younger generation. This study aims to examine how the game of soccer can serve as an integrative medium in learning Pancasila and Civic Education (PPKn) at the elementary school level. Using a descriptive qualitative approach, data were collected through observation, interviews with teachers, and documentation of activities that integrate soccer activities with Civics materials. The research findings revealed that the dynamics in soccer games, such as team collaboration, sportsmanship, adherence to rules, and respect between players, naturally reflect the values of Pancasila, especially the 2nd (humanity), 3rd (unity), and 5th (social justice) precepts. Teachers play an important role in helping students reflect on their playing experiences and relate them to the application of Pancasila values in daily life. In conclusion, integrating soccer games in Civics lessons can be a relevant, fun, and effective teaching method to instill noble Pancasila values in students in elementary schools